NOSOLOGICAL PROFILE IN A DERMATOLOGY REFERENCE CENTER - de Alencar Diógenes Rôla, Clarissa (2023)
To analyze the nosological profile of patients referred from primary care to a center specialized in dermatology. Cross-sectional study with a descriptive analytical approach. The sample consisted of 154 patients, who underwent detailed anamnesis and physical examination. The mean age was 45 years and the majority were female 115 (74.7%). The waiting time for referral from the health center to specialized care had an average of six months, being motivated by diagnosis and treatment in 104 (67.5%). It was diagnosed at the first visit in 141 (91.6%) and no additional tests were necessary in 106 (70.7%). The most common diagnoses were: acne 13(8.4%), psoriasis 11(7.1%) and seborrheic keratosis 10(6.5%). The results reinforce the importance of the dermatological diagnosis, which can be very extensive, but which is eminently clinical. The data can help in the development of prevention and control strategies for the most frequent pathologies.